Comparative calibrations of measuring microphones performed in a free field - Wszołek, Grażyna; Barwicz, Wiesław (Archives of Acoustics, 2007)
Comparison of calibrations of measuring microphones obtained in two laboratories – Laboratoryof Physikalisch-Technische Bundesanstalt in Braunschweig (Germany) and Laboratoryof Vibroacoustics at the University of Science and Technology in Kraków (Poland) is presentedin the paper. However, the performed calibrations were not the official Inter-LaboratoryComparisons (ILC), since those comparisons in the field of Calibrations of reference microphonesin a free field are still at the preparatory stage.The paper contains comparisons of the calibration results (together with uncertainty ofmeasurements) obtained in both laboratories for exactly the same devices as well as the traceabilityof the results. According to the guidelines of the Polish Centre for Accreditation –given in the DA-05 document – the index $E_n$ constitutes the assessment criterion.The selected problems related to calibrations and influencing their results – are discussedby the authors. They have drawn a special attention to comparisons of the calibration resultsobtained in various laboratories. Those problems are connected – among others – with the lackof basic data in the Calibration Certificates concerning e.g. traceability of the results, referencemicrophones, methods of measurements and uncertainty of measurements assessments.The paper contains suggestions concerning further co-operation of laboratories in this field.